Let k = 5. What is the value of 27 – k · 2?

A.
11

B.
17

C.
24

D.
44

Answers

Answer 1
Answer: Given:  27-k · 2 = n

Solution: 27-5 ·2 = n
               22 · 2 = n

Answer: 44 option D

Related Questions

Write the missing value above the variable. M-9=7
A mutual fund’s net asset value increases by $5 per share. An investor who owns 450 shares of this fund sells them all for a profit of $2,205. What can you conclude about the fund?
What is the volume, in cubic cm, of a cylinder with the height of 16cm and a base radius of 3 cm, to the nearest tenths place?
Mandy and Jordan each bought some of the same notebooks and the same three-ring binder. Mandy paid $5.85 for 3 notebooks and 1 binder. Jordan paid $4.65 for2 notebooks and 1 binder. What is the price of one ofthe notebooks?
Solve the inequality. |3x + 6| < 12A. –6 > x > 2 B. –2 < x < 2 C. –6 < x < 2 D. –21 < x < 3

The function f(t) = t2 + 6t − 20 represents a parabola.Part A: Rewrite the function in vertex form by completing the square. Show your work. (6 points)

Part B: Determine the vertex and indicate whether it is a maximum or a minimum on the graph. How do you know? (2 points)
The function H(t) = −16t2 + 90t + 50 shows the height H(t), in feet, of a projectile after t seconds. A second object moves in the air along a path represented by g(t) = 28 + 48.8t, where g(t) is the height, in feet, of the object from the ground at time t seconds.

Part A: Create a table using integers 1 through 4 for the 2 functions. Between what 2 seconds is the solution to H(t) = g(t) located? How do you know? (6 points)

Part B: Explain what the solution from Part A means in the context of the problem. (4 points)

Answers

Part A: f(t) = t² + 6t - 20
              u = t² + 6t - 20
         + 20            + 20
      u + 20 = t² + 6t
u + 20 + 9 = t² + 6t + 9
      u + 29 = t² + 3t + 3t + 9
      u + 29 = t(t) + t(3) + 3(t) + 3(3)
      u + 29 = t(t + 3) + 3(t + 3)
      u + 29 = (t + 3)(t + 3)
      u + 29 = (t + 3)²
          - 29       - 29
              u = (t + 3)² - 29

Part B: The vertex is (-3, -29). The graph shows that it is a minimum because it shows that there is a positive sign before the x²-term, making the parabola open up and has a minimum vertex of (-3, -29).
------------------------------------------------------------------------------------------------------------------
Part A: g(t) = 48.8t + 28           h(t) = -16t² + 90t + 50
            | t |   g(t)  |                          |  t  |  h(t)  |
            |-4|-167.2|                          | -4 | -566 |
            |-3|-118.4|                          | -3 | -364 |
            |-2| -69.6 |                          | -2 | -194 |
            |-1| -20.8 |                          | -1 |  -56  |
            |0 |   -28  |                          |  0  |   50  |
            |1 |  76.8 |                          |  1  |  124 |
            |2 | 125.6|                          |  2  | 166  |
            |3 | 174.4|                          |  3  | 176  |
            |4 | 223.2|                          |  4  | 154  |
The two seconds that the solution of g(t) and h(t) is located is between -1 and 4 seconds because it shows that they have two solutions, making it between -1 and 4 seconds.

Part B: The solution from Part A means that you have to find two solutions in order to know where the solutions of the two functions are located at.

The correct answers are:

Question 1 - Part A: f(t)=(t+3)²-29; Part B: (-3, -29), minimum; Question 2 - Part A: H(1) = 124, g(1) = 76.8; H(2) = 166, g(2) = 125.6; H(3) = 176, g(3) = 174.4; H(4) = 154, g(4) = 223.2; Part B: Between 3 and 4 seconds, because that is where the values of g(t) catch up with H(t).

Explanation:

Our quadratic function is in the form f(x)=ax²+bx+c. Our value of a is 1, b is 6, and c is -20.

To write a quadratic in vertex form, first take half of the b value and square it: (6/2)² = 3² = 9. This is what we will add and subtract to the function:

f(t) = t²+6t+9-20-9

The squared portion will be (t+b/2)²:

f(t) = (t+3)²-20-9

f(t) = (t+3)²-29

Vertex form is f(x) = a(x-h)²+k, where (h, k) is the vertex; in our function, (h, k) is (-3, -29).

Since the value of a was a positive, this parabola opens upward; this makes the vertex a minimum.

For Question 2 Part A, substitute the values 1, 2, 3 and 4 in H(t) and g(t).

For Part B, we can see that the values of g(t) are much less than that of H(t) until 3 seconds. From there, we can see that g(t) passes H(t). This means that the solution point, where they intersect, is between 3 and 4 seconds.

A certain species of tree grows an average of 3.1 cm per week. Write an equation for the sequence that represents the weekly height of this tree in centimeters if the measurements begin when the tree is 400 centimeters tall.

Answers

Answer:

y = 3.1x+400c

Step-by-step explanation:

Slope intercept form:

The equation of straight line is given by:

y =mx+b            ....[1]

where, m is the rate or slope and b is the initial value of y-intercept.

As per the statement:

A certain species of tree grows an average of 3.1 cm per week.

Let x be the number of week and y represents the weekly height of the tree.

then;

" tree grows an average of 3.1 cm per week." translated to 3.1 x

It is also given that:

the measurements begin when the tree is 400 centimeters tall.

⇒y(0) =b = 400 cm

Substitute the given values in [1] we have;

y = 3.1x+400

Therefore, an equation for the sequence that represents the weekly height of this tree in centimeters is, y = 3.1x+400

Y = 400 + 3.1x

X for the number of weeks
Y for total CM

Hope this helps...

Amelia is stacking identical cube-shaped boxes. She stacks 8boxes to make a tower that is 112 cm tall. She adds 1 more
box to the tower. How tall is the tower now? Give your answer
in centimetres (cm).

Answers

Answer:

126 cm

Step-by-step explanation:

each block is 112/8 cm tall=14cm

112cm is the current tower

add one more block +14cm is 126 cm total

Jai earns $9.75 per hour. Jai works 3 hours one day and then works 7 hours the next day

Answers

Answer:

97.50

Step-by-step explanation:

9.75(3) + 9.75(7);

9.75(3+7); 97.50

Given the geometric series:16+2+1/4... find the sum of the geometric progression up to the 6th term​

Answers

The sum of the geometric progression up to the 6th term is 512/7

To find the sum of a geometric series, you can use the formula for the sum of a finite geometric series:

\[S_n = (a(1 - r^n))/(1 - r)\]

Where:

- Sₙ is the sum of the first n terms of the series.

- a is the first term of the series.

- r is the common ratio.

- n is the number of terms in the series.

In your case, you have the geometric series: 16, 2, 1/4, ...

1. Identify the values for the formula:

  - The first term (a) is 16.

  - The common ratio (r) is found by dividing the second term by the first term: 2/16 = 1/8.

  - You want to find the sum of the first 6 terms (n = 6).

2. Plug these values into the formula and calculate S₆:

S₆ = (16(1 - (1/8)⁶))/(1 - 1/8)

Now, calculate the individual terms in the formula:

S₆ = (16(1 - 1/262144))/(7/8)

S₆ = (16(262143/262144))/(7/8)

S₆ = ((4194288/262144)/(7/8)

Now, perform the division:

S₆ = (4194288/262144) \* (8)/(7)

S₆ = 64 * 8/7

Now, multiply:

S₆ = 512/7

So, the sum of the geometric progression up to the 6th term is 512/7

Learn more about geometric series here

brainly.com/question/31472659

#SPJ1

If f(x) = 5-2x find f(9)+ 3

Answers

f (9) = 5 - 2 (9)

f (9) = 5 - 18

f (9) = - 13

f (9) + 3 = - 13 + 3

f (9) + 3 = - 10

Answer:

the answer is -10

Step-by-step explanation: